1998
DOI: 10.1590/s0100-879x1998001100016
|View full text |Cite
|
Sign up to set email alerts
|

Using green fluorescent protein to understand the mechanisms of G-protein-coupled receptor regulation

Abstract: G protein-coupled receptor (GPCR) activation is followed rapidly by adaptive changes that serve to diminish the responsiveness of a cell to further stimulation. This process, termed desensitization, is the consequence of receptor phosphorylation, arrestin binding, sequestration and down-regulation. GPCR phosphorylation is initiated within seconds to minutes of receptor activation and is mediated by both second messenger-dependent protein kinases and receptor-specific G proteincoupled receptor kinases (GRKs). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Both the extent and kinetics of agonist‐induced translocation were enhanced by co‐transfection of GRK2. Equivalent results were produced with transient expression of the dopamine D 1A receptor (Barak et al ., 1997) and in review (Ferguson, 1998; Ferguson et al ., 1998) these authors have indicated that the basic features of agonist‐induced β‐arrestin 2‐GFP translocation can be observed for a wide range of GPCRs. One GPCR which is highly resistant to agonist‐induced short‐term desensitization is the gonadotrophin releasing hormone (GnRH) receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Both the extent and kinetics of agonist‐induced translocation were enhanced by co‐transfection of GRK2. Equivalent results were produced with transient expression of the dopamine D 1A receptor (Barak et al ., 1997) and in review (Ferguson, 1998; Ferguson et al ., 1998) these authors have indicated that the basic features of agonist‐induced β‐arrestin 2‐GFP translocation can be observed for a wide range of GPCRs. One GPCR which is highly resistant to agonist‐induced short‐term desensitization is the gonadotrophin releasing hormone (GnRH) receptor.…”
Section: Introductionmentioning
confidence: 99%
“…GPCRs can be activated by multiple ligands and exhibit the capacity to couple to numerous intracellular signal transduction pathways (18). Oxidative stresses have recently been shown to be generated by agonists of several members of the GPCR superfamily (19).…”
Section: Discussionmentioning
confidence: 99%
“…The sites of phosphorylation have been mapped mainly to the C-terminal tail and have been linked regulatory processes, such as desensitization and internalization [11]. The D-R-Y sequence, positions at 145-147, is highly conserved (Fig.…”
Section: Sequences Analysis Of Mvtrmentioning
confidence: 99%